WORK SATISFACTION IMPROVED BY INCREASING THE QUALITY OF EMOTIONAL INTELLIGENCE - Hidayat, Amelia Julianti (JURISMA : Jurnal Riset Bisnis & Manajemen, 2020)
In 2014, PT. X was facing an income loss. It was affected by the changes in the global economic circumstances. The impact has a strong influence on a few company's aspects, one of them is the human resources aspect, such as the decrease in wages and benefits that resulting in the decrease of PT. X employees' job satisfaction. With high employees' emotional intelligence, job satisfaction should be maximally reached. The purpose of this research is to find out the achievement of employees' job satisfaction through emotional intelligence at PT. X. The methods used in this research were descriptive method (qualitative) with respondent’s analysis and verificative method (quantitative) using statistical tests analysis: linear regression analysis, coefficient determination analysis, and hipothetical test. The result shows that employees' job satisfaction can be achieved significantly through emotional intelligence. Keywords: Job Satisfaction, Emotional Intelligence